(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
This research article delves into the use of Task-Based Language Teaching (TBLT) as a way to improve sociolinguistic competence among university students learning English as a Foreign Language (EFL) in Uzbekistan. Sociolinguistic competence is essential for effective communication, enabling learners to interact appropriately across various social and cultural situations. Despite efforts to adopt more communicative teaching methods, many EFL classrooms in Uzbekistan still focus heavily on grammar, often neglecting the pragmatic skills students need. To address this gap, a quasi-experimental study was conducted with 36 undergraduate students, using classroom tasks designed to enhance their understanding of language in context. By employing a mixed-methods approach, the study analyzed pre- and post-tests, recordings of student interactions, and interviews. The results revealed a notable improvement in how students used politeness strategies, controlled language registers, and employed pragmatic routines. The article ultimately calls for significant changes in the curriculum, better teacher training, and the integration of TBLT to help align Uzbekistan’s language education with global communication standards, fostering a more effective and context-aware learning experience for students.